Pure-helium 3D model atmospheres of white dwarfs - Cukanovaite, Elena; Tremblay, Pier-Emmanuel; Ludwig, Hans-Günter (Arxiv, 2018)
We present the first grid of 3D simulations for the pure-helium atmospheres of DB white dwarfs. The simulations were computed with the CO5BOLD radiation-hydrodynamics code and cover effective temperatures and surface gravities between 12000 K < Teff < 34000 K and 7.5 < log(g) (cgs units) < 9.0, respectively. In this introductory work, synthetic spectra calculated from the 3D simulations are compared to appropriate 1D model spectra under a differential approach. This results in the derivation of 3D corrections for the spectroscopically derived atmospheric parameters of DB stars with respect to the 1D ML2/alpha = 1.25 mixing-length parameterisation. No significant Teff corrections are found for the V777 Her instability strip region, and therefore no 3D revision is expected for the empirical blue and red edges of the strip. However, large log(g) corrections are found in the range 12000 K < Teff < 23000 K for all log(g) values covered by the 3D grid. These corrections indicate that 1D model atmospheres overpredict log(g), reminiscent of the results found from 3D simulations of pure-hydrogen white dwarfs. The next step will be to compute 3D simulations with mixed helium and hydrogen atmospheres to comprehend the full implications for the stellar parameters of DB and DBA white dwarfs.
Gesehen am 13.10.2020